Prevalence of genital Chlamydia trachomatis among women of reproductive age attending outpatient clinic at Kisumu County Referral Hospital, Kenya, 2021 - Martha Nyakambi; Anthony Waruru; Adesina Oladokun (AOSIS, 2022)
Background. Chlamydia trachomatis is a common a sexually transmitted infections (STI). Asymptomatic Chlamydia is undetectable because it is asymptomatic. In Kenyan women ages 18 to 49, the disease is poorly understood. Methods. This cross-sectional study was conducted at Kisumu County Referral Hospital, Kenya. 385 women consented and completed the electronic questionnaire. The women then provided vaginal swab samples which were tested for Chlamydia trachomatis using Chlamydia rapid diagnostic test kit. Results. A total of 29 (7.5%) patients tested positive and were given medication. 65.2% of 385 participants were 18-25, with 5.7% prevalence. Women preferred self vaginal swab collection over health worker collection (0.3%). Multiple sexual partners, coinfection with other STIs, and upper tract infections are linked to genital Chlamydia. 92% of participants didn't know Chlamydia's effects. Conclusions. The study's prevalence of genital Chlamydia trachomatis was within previous estimates. Populations and screening methods vary. Patient and community education about genital Chlamydia infection is needed. Multiple sexual partners, marital status, education, and STI history are risk factors. Most women preferred self vaginal swab collection.